Sublethal mechanical shear stress increases the elastic shear modulus of red blood cells but does not change capillary transit velocity. (25th August 2020) - McNamee, Antony P.; Tansley, Geoff D.; Simmonds, Michael J.
Abstract: Blood exposure to supraphysiological shear stress within mechanical circulatory support is suspected of reducing red blood cell (RBC) deformability and being primal in the pathogenesis of several secondary complications. No prior works have explored RBC dynamics with the resolution required to determine shear elastic modulus, and/or cell capillary velocity, following exposure to mechanical stresses. Healthy RBCs were exposed to 0, 5, 50, and 100 Pa in a Couette shearing system. For comparison, blood was also exposed to heat treatment—a method that predictably increases RBC rigidity. Shear modulus assessment required aspiration of single RBCs through narrow micropipettes at known suction force. Cell transit velocities were measured within microchannels in regions of fully developed flow. Supraphysiological shear stress increased the elastic shear modulus by 39% and 69% following exposure to 50 and 100Pa, respectively. Cell transit velocity, however, did not change following shear, with concurrent decreases in cell volume likely nullifying increased shear modulus‐friction interactions. Differences observed were consistent with our internal control (heat treatment), supporting that cell mechanics are significantly impaired following supraphysiological‐sublethal shear exposure. Given mechanical circulatory support operates at shear stresses consistent with the present study, it is plausible that these devices induce fundamental impairment to the material properties of RBCs.